The development of nutrient pools along two holocene chronosequences with contrasting bedrocks in the Swiss Alps - Greinwald, Konrad; Musso, Alessandra; Scherer-Lorenzen, Michael; Weiler, Markus; Egli, Markus (Catena, 2023)
Climate change accelerates glacial retreat worldwide, leaving large areas of unconsolidated terrain. Glacial retreat opens the possibility to study the temporal development of ecosystems, their functions and services by use of a space-for-time-approach. Nutrient pools are important indicators of various ecosystem services as they are critical in supporting the establishment and growth of plant communities, which in turn support the food webs and ecological processes that sustain the ecosystem and downstream communities. In this study, we examined the temporal development of nutrient pools in soils and vegetation communities over a period of more than 10,000 years. We analyzed a comprehensive dataset that embraces repeated measurements of carbon (C), nitrogen (N), potassium (K), calcium (Ca), magnesium (Mg) and phosphorous (P) pools in above- and belowground biomass, litter and soil across alpine chronosequences from two glacier forelands with contrasting bedrocks (silicate vs carbonate). We found that total nutrient pools of C and N, being closely linked to the biomass, increased rapidly along both chronosequences, whereas nutrient pools of K, Ca, Mg, and P were large at first and decreased steadily with time, though at different rates related to the two parent materials. We also observed a remarkable difference in the P pool development between the two glacier forelands. The calcareous soils started out with much more P than the siliceous locations. The plant availability of P was, however, higher in the siliceous soils due to the neutral pH, but decreased with acidification. In the calcareous soils, plant P availability was low at the beginning due to a high pH, but improved as decalcification progressed and pH lowered to slightly acidic conditions. The results of this work highlight that assessing the temporal development of ecosystems services using long-term proglacial chronosequences enhances our understanding of landscape evolution.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Chronosequence; Glacier foreland; Nutrients; Pedogenesis; Primary succession; Swiss Alps